2020
DOI: 10.1088/1361-648x/ab7fdc
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of magnetoelectric coupling in Cr doped Mn2O3

Abstract: The effect of Cr doping with nominal compositions Mn 2-x Cr x O 3 (0  x  0.10) has been undertaken to investigate its effect on structural, magnetic, dielectric and magnetoelectric properties. The Cr doping transformed the room temperature crystal structure from orthorhombic to cubic symmetry. Similar to -Mn 2 O 3 , two magnetic transitions have been observed in the Cr doped samples. The effect of Cr doping is significant on the low temperature transition i.e. the lower magnetic transition shifted towards h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…Synthetic manganese oxides and manganese oxide minerals play an important role in different technological processes and applications. , For example, some of them are utilized as effective catalysts, as supercapacitors, as ferroelectrics or multiferroics, as elements in ion batteries, as semiconductors, and for many other purposes. In general, manganese oxides, including Mn-based perovskites, are inexpensive and highly functional materials, which combine interesting electronic and magnetic properties and, therefore, have remained in the focus of recent investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic manganese oxides and manganese oxide minerals play an important role in different technological processes and applications. , For example, some of them are utilized as effective catalysts, as supercapacitors, as ferroelectrics or multiferroics, as elements in ion batteries, as semiconductors, and for many other purposes. In general, manganese oxides, including Mn-based perovskites, are inexpensive and highly functional materials, which combine interesting electronic and magnetic properties and, therefore, have remained in the focus of recent investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The detail discussion about this feature is given in [6]. Recently, we have observed that at RT Mn 1.90 Cr 0.10 O 3 (MCO) crystallized in cubic symmetry with Ia-3 space group and exhibit large magnetodielectric effect as compared to pristine Mn 2 O 3 [8]. The dc magnetic susceptibility of MCO also shows two magnetic transitions as observed for parent compound.…”
Section: Introductionmentioning
confidence: 76%
“…phenomena always emerge during the phase transition process. In recent years, manganese oxide Mn 2 O 3 is studied for its intriguing magnetic and dielectric properties [6][7][8]. The manganese oxide is also one of the important ingredients for multiferroic materials which offers the existence of two or more primary ferroic orders in single material and their tunability; especially magnetoelectric coupling.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some results on Zn-doped manganese oxide nanoparticles for various applications reported in the literature [31]. Chandraet al [32] reported the consequences of Cr doping on the various properties of Mn 2 O 3 nanoparticles such as structural, dielectric, magneto-electric and magnetic properties. It has been observed that the symmetry changes to cubic with Cr doping from orthorhombic at room temperature.…”
Section: Introductionmentioning
confidence: 99%